The costs of regulatory barriers to trade in services New estimates of ad valorem tariff equivalents - Benz, Sebastian (OECD Trade Policy Papers, 2020)
This paper presents new estimates of policy-induced trade costs in five services sectors for 46 countries. Results demonstrate the significant untapped economic potential of multilateral, plurilateral, and unilateral services trade liberalisation. Even though services trade has more than tripled in the last two decades, the results show that trade costs are still high. The results are not only interesting in and of themselves, but they can also be used as input for further analysis on the economic benefits from different scenarios regarding the dismantling of barriers to trade in services. This paper exploits recent advances related to the measurement of services barriers in the OECD Services Trade Restrictiveness Index (STRI)